Disseminated intravascular coagulation in catastrophic antiphospholipid syndrome: clinical and haematological characteristics of 23 patients. Issue 6 (16th May 2005) - Asherson, R A; Espinosa, G; Cervera, R; Gómez-Puerta, J A; Musuruana, J; Bucciarelli, S; Ramos-Casals, M; Martínez-González, A L; Ingelmo, M; Reverter, J C; Font, J; Triplett, D A
Abstract : Background: Disseminated intravascular coagulation (DIC) is an acquired syndrome characterised by formation of microthombi and fibrin deposition in the microvasculature. The catastrophic antiphospholipid syndrome (APS) is characterised by multiorgan thrombosis, mainly involving small vessels. A broad spectrum of disorders may develop DIC features; however, the catastrophic APS has not previously been recognised as a cause of DIC. Objective: To analyse the clinical and laboratory characteristics of catastrophic APS patients with DIC features. Methods: The web site based international registry of patients with catastrophic APS (CAPS registry) (http://www.med.ub.es/MIMMUN/FORUM/CAPS.HTM ) was analysed and the cases with DIC features selected. Results: In 173 patients with catastrophic APS, 23 (13%) were found with DIC features. The clinical and immunological characteristics were similar in catastrophic APS patients with and without DIC features; a significant difference was found only in the prevalence of thrombocytopenia (100% in patients with DIC features v 59% in those without DIC features). Conclusions: DIC features are not rare in catastrophic APS, supporting the need for systematic screening of antiphospholipid antibodies in all patients with DIC features without precipitating factors. The presence of DIC features in the context of an APS makes it imperative to rule out the catastrophic variant of this syndrome.